2015
DOI: 10.1038/srep15991
|View full text |Cite
|
Sign up to set email alerts
|

Forest soil carbon is threatened by intensive biomass harvesting

Abstract: Forests play a key role in the carbon cycle as they store huge quantities of organic carbon, most of which is stored in soils, with a smaller part being held in vegetation. While the carbon storage capacity of forests is influenced by forestry, the long-term impacts of forest managers’ decisions on soil organic carbon (SOC) remain unclear. Using a meta-analysis approach, we showed that conventional biomass harvests preserved the SOC of forests, unlike intensive harvests where logging residues were harvested to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
98
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(123 citation statements)
references
References 37 publications
(66 reference statements)
12
98
1
1
Order By: Relevance
“…Thinning reduced the SOC concentrations except for in October, which was partially consistent with our hypothesis, and the thinning effect was more pronounced in the upper soil layer than in the lower. An average SOC loss of 32.5% SOC in thinned sites was also found by Boerner et al (2006), whereas Achat et al (2015) found an SOC decrease of approximately 7% by tree removal in a meta-analysis. The decrease in SOC following the partial removal of canopy trees has been attributed to the reduction in the supply of substrate that enters the soil (Piene and Cleve, 1978;Jandl et al, 2007).…”
Section: Soil Organic Carbonmentioning
confidence: 96%
See 1 more Smart Citation
“…Thinning reduced the SOC concentrations except for in October, which was partially consistent with our hypothesis, and the thinning effect was more pronounced in the upper soil layer than in the lower. An average SOC loss of 32.5% SOC in thinned sites was also found by Boerner et al (2006), whereas Achat et al (2015) found an SOC decrease of approximately 7% by tree removal in a meta-analysis. The decrease in SOC following the partial removal of canopy trees has been attributed to the reduction in the supply of substrate that enters the soil (Piene and Cleve, 1978;Jandl et al, 2007).…”
Section: Soil Organic Carbonmentioning
confidence: 96%
“…A major focus in forest management is to promote the increase of this sink (Jandl et al, 2007;Achat et al, 2015;Moreno-Fernandez et al, 2015). Soil organic carbon (SOC) can be divided into labile and recalcitrant fractions based on the mean residence times in the soil.…”
Section: Introductionmentioning
confidence: 99%
“…Johnson & Curtis (2001) reported that whole-tree harvesting resulted in slight decreases in soil organic carbon stock (-6%) while sawlog harvesting increases (18%) the soil carbon stock in the A horizon. Achat et al (2015) stated that conventional harvesting of tree stems (sawlog) reduced the forest floor carbon stock by 22% in comparison to unharvested stands, but no effects were found in the mineral soil organic carbon stock. When intensive harvesting was considered (whole-tree harvesting), the forest floor carbon stock was reduced by 37% and mineral soil carbon stock was mainly affected in the deeper layers (-7%).…”
Section: Harvesting Operationsmentioning
confidence: 99%
“…The highest proportion of terrestrial carbon is stored in forest ecosystems [1]. Thus forests are important to balance global carbon dioxide (CO 2 ) [2][3][4]. Human activities are important considerations because land use change and forest management directly affect the forest conditions and thus the carbon cycle.…”
Section: Introductionmentioning
confidence: 99%